Redundancy and Specificity of Type VI Secretion vgrG Loci in Antibacterial Activity of Agrobacterium tumefaciens 1D1609 Strain - Santos, Mary Nia M.; Cho, Shu-Ting; Wu, Chih-Feng; Chang, Chun-Ju; Kuo, Chih-Horng; Lai, Erh-Min (Frontiers in Microbiology, 2020)
Type VI secretion system (T6SS) is a contractile nanoweapon employed by many Proteobacteria to deliver effectors to kill or inhibit their competitors. One T6SS gene, vgrG, encodes a spike protein for effector translocation and is often present as multiple copies in bacterial genomes. Our phylogenomic analyses sampled 48 genomes across diverse Proteobacteria lineages and found ~70% of them encode multiple VgrGs, yet only four genomes have nearly identical paralogs. Among these four, Agrobacterium tumefaciens 1D1609 has the highest vgrG redundancy. Compared to A. tumefaciens model strain C58 which harbors two vgrG genes, 1D1609 encodes four vgrG genes (i.e. vgrGa-d) with each adjacent to different putative effector genes. Thus, 1D1609 was selected to investigate the functional redundancy and specificity of multiple vgrG genes and their associated effectors. Secretion assay of single and multiple vgrG deletion mutants demonstrated that these four vgrGs are functionally redundant in mediating T6SS secretion. By analyzing various vgrG mutants, we found that all except for the divergent vgrGb could contribute to 1D1609’s antibacterial activity. Further characterizations of putative effector-immunity gene pairs revealed that vgrGa-associated gene 2 (v2a) encodes an AHH family nuclease and serves as the major antibacterial toxin. Interestingly, C58’s VgrG2 shares 99% amino acid sequence identity with 1D1609’s VgrGa, VgrGc and VgrGd. This high sequence similarity allows 1D1609 to use an exogenous VgrG delivered from C58 to kill another competing bacterium. Taken together, Agrobacterium can use highly similar VgrGs, either produced endogenously or injected from its close relatives, for T6SS-mediated interbacterial competition.